The Commitment of Special School Teachers Towards The Implementation of Distance Learning During the Covid-19 Pandemic - Subagya, Subagya (LPPM Undiksha, 2022)
The COVID-19 pandemic is a challenge for teachers to keep learning. One alternative that teachers can do is distance learning. The continuity of learning is largely determined by the commitment of the teacher. The purpose of this study is to reveal the contribution of teacher commitment to the continuity of learning, as well as to find out the effective contribution and relative commitment of teachers to learning in special schools. This research approach is quantitative research. The sampling technique used is accidental sampling, where the determination of the sample is based on chance, anyone who responds to the researcher can be used as a sample. Data collection techniques using a questionnaire. The teacher commitment instrument was adapted from the commitment scale developed by Allen and Meyer which has sufficient validity and reliability. The learning instrument uses content validity, and the instrument reliability uses the interrater technique. Questionnaires were sent via WhatsApp to all teacher communities throughout Indonesia which were limited to 3 days and collected 872 respondents. The data were analyzed by multiple regression with the help of SPSS 23. The results showed that the teacher's commitment to the implementation of distance learning was influenced by the teacher's commitment by 2.5% and influenced by other variables not included in the linear regression model by 97.5%. Normative commitment has an effective contribution (1.31%) and a relative contribution (51.77%), which is the largest contribution compared to the other two aspects of commitment.